2006
DOI: 10.1166/jnn.2006.416
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Liposomal Insulin

Abstract: There have been several attempts published in the literature related with orally effective insulin formulations, which are increasing in popularity. Some of the results indicate that it is possible to reduce blood glucose level by orally administered liposomal insulin formulations, but there is general need to understand the mechanism and effective components of the liposome formulations. In our study, liposomal insulin formulations were prepared using insulin (Humulin R) or protamine- containing insulin (Humu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Several attempts have been made to improve the potency of insulin-loaded liposomal systems, e.g., insulin and protamine-containing insulin, respectively, were formulated with a cholesterol, dipalmitoyl phosphatidylcholinecholesterol (DPPC) mixture, and mucoadhesive agent (methyl cellulose (MC))-added DPPC-cholesterol mixture (15). The liposomal insulin was given to mice and rats by gavage; subsequently, reduced blood glucose levels were observed.…”
Section: Oral Liposomesmentioning
confidence: 99%
“…Several attempts have been made to improve the potency of insulin-loaded liposomal systems, e.g., insulin and protamine-containing insulin, respectively, were formulated with a cholesterol, dipalmitoyl phosphatidylcholinecholesterol (DPPC) mixture, and mucoadhesive agent (methyl cellulose (MC))-added DPPC-cholesterol mixture (15). The liposomal insulin was given to mice and rats by gavage; subsequently, reduced blood glucose levels were observed.…”
Section: Oral Liposomesmentioning
confidence: 99%
“…Caco-2 cell line is widely used as an in vitro model for evaluating oral drug absorption (23,(51)(52)(53)(54). The medium used in Caco-2 transport in our experiments PG/DMEM (60%/ 40%) was also tested, and Caco-2 cell viability of the medium was found to be 77.4%.…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, these systems were developed for oral administrations. Caco-2 cell line has been used as a model in absorption studies (23). Therefore, permeability experiments were performed using caco-2 cell lines to understand how formulations delivered raloxifene through biological membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The liposomal composition, EE, rate of drug release from lipid bilayers, size and surface charge are all important factors in successful liposomal drug delivery [28]. Degim et al have reported a signifi cant reduction in BGLs in diabetic rats on oral administration of liposomal insulin [29]. Further investigations with liposomes containing insulin in rats and dogs showed reduction in BGLs.…”
Section: Liposomesmentioning
confidence: 99%